Konsep Pembelajaran Pendidikan Islam Prespektif Pemikiran Ibnu Sina - Aminul Yaqin (Maharot : Journal of Islamic Education, 2022)
education system is the adoption of Western educational theories. While the theories of Islamic education sometimes often abandoned or ignored don't even know the difference between theory at all education that comes from the West and which one comes from the Islamic world. even though There are quite basic differences between Western and Islamic educational theory. Therefore, we need to re-examine the views of philosophers about the concept of education, including the concept of education by Ibn Sina. His concept of thinking about education can be seen through objectives, materials, methods, educators and punishments. On Basically, the concept is still very actual and relevant to the development of modern education today. so that in this paper seeks to explain how the concept of Islamic education according to Ibn Sina, so that Muslim countries can implement such education, especially education in Indonesia. In order to be able to describe some of the problem formulations above, the author uses a descriptive-analytic method to the literature related to the problems discussed in this paper.